Developing Vocabulary By Contextualizing: an Effective Way for Retention - Latha Mutyaboyina (International Conference on Education and Language (ICEL), 2013)
Necessity is the mother of invention.  Since time immemorial man has advanced and made mammoth technological leap due to the necessities and making the appropriate adjustments and inventions. Working in an engineering college which caters to the eclectic mix of students from various regions of our country with different financial, social, cultural and educational backgrounds and gave keen urge to find methods of teaching which in turn would help them to get language competence and communicative competence.  When an individual acquires these competencies it will definitely boost the confidence and morale of the person.  Vocabulary development is the glue that holds fluency together.  Fluency has been defined as the freedom from word identification problems that might hinder comprehension. (Pakulski& Chard 2005)